THE URGENCY OF LEARNING INNOVATION ON ISLAMIC RELIGIOUS STUDY (URGENSI INOVASI PEMBELAJARAN DALAM PENDIDIKAN AGAMA ISLAM): Learning Innovation, Islamic Religious Study, Learning Method - ALI MIFTAKHU ROSYAD (al-Afkar, Journal For Islamic Studies, 2019)
This article aims to explore the urgency of learning innovation in Islamic religious education. Learning innovation is a strategy that is structured as well as pposible to answer various kinds of learning problems. The Progressiveness in science and technology is increasingly dynamic and sustainable as a result of modernization and globalization. Learning of Islamic religious education requires innovation to answer various kinds of problems which occur in society. The learning that utilizes information technologies in formal education is named E-learning. One of the advantages is that students can learn about teaching materials any time and anywhere if needed, considered teaching materials are stored on the computer. While one disadvantage is the decreased interaction between teachers and students or even between students themselves. Therefore, the expected out come from learning of islamic religious education should be had the competencies that are required by stakeholder needs, which should fulfill professional needs, social needs, industrial needs, and aspects of scientific vision. Thus, the nation has skilled human resources and be able to compete both locally and internationally. Artikel ini bertujuan untuk mengeksplorasi urgensi inovasi pembelajaran dalam pendidikan agama islam.inovasi pembelajaran merupakan suatu strategi yang disusun sedemikian rupa untuk menjawab berbagai macam permasalahan pembelajaran. Kemajuan dalam bidang ilmu pengetahuan dan teknologi semakin dinamis dan berkelanjutan sebagai akibat dari modernisasi dan globalisasi. Pembelajaran pendidikan agama islam memerlukan inovasi untuk menjawab berbagai macam persoalan yang terjadi di masyarakat. Pembelajaran yang memanfaatkan teknologi informasi dalam pendidikan formal disebut E-learning. Salah satu kelebihannya adalah peserta didik dapat belajar tentang bahan ajar setiap saat dan di mana saja kalau diperlukan mengingat bahan ajar tersimpan di komputer. Sedangkan salah satu kekurangannya adalah kurangnya interaksi antara guru dan siswa atau bahkan antar siswa itu sendiri. Dengan demikian out come yang diharapkan dari pembelajaran PAI adalah harus mempunyai kompetensi yang sesuai dengan kebutuhan stakeholder, yaitu harus memenuhi kebutuhan profesional (profesional needs), kebutuhan masyarakat (social needs), kebutuhan dunia kerja (industrial needs), dan kebutuhan generasi masa depan (aspek scientific vision). Sehingga, bangsa ini memiliki SDM yang terampil dan mampu berdaya saing baik lokal maupun internasional.